Penyuluhan Pentingnya Mengkonsumsi Makanan Bergizi Seimbang dalam Upaya Peningkatan Status Gizi Ibu Hamil - Rahmadhani, Sendy Pratiwi; Anggraini, Arie; Rahmawati, Eka (Borneo Community Health Service Journal, 2024)
Pregnant women are included in the nutrient-vulnerable group, so it is recommended to increase nutrient intake to meet the nutritional needs of mothers and fetuses, achieving the nutritional status of pregnant women in a normal state. Mother's knowledge about nutrition will affect the dishes and the quality of the food consumed. The form of implementation of this community service activity is in the form of counseling on the importance of consuming balanced nutrition to improve the nutritional status of pregnant women. The delivery of material was carried out by the lecture method using powerpoint, leaflet and table of the "Fill My Plate" meal. This activity was attended by 30 pregnant women and was carried out in TPMB Faulien, S.ST. Palembang city. The evaluation of the activity was carried out by providing a pre-post test nutritional knowledge questionnaire. Based on the results of the analysis, participants who belonged to the category of poor knowledge decreased to 20% and participants who belonged to the category of good knowledge increased to 80%. Counseling has been proven to be effective in increasing pregnant women's understanding of balanced nutritious food.